Eight MeV per charge state from 300 ps laser ion acceleration by using micrometric foils. Issue 3 (1st December 2020) - Torrisi, Lorenzo; Cutroneo, Mariapompea; Torrisi, Alfio
Abstract: Proton acceleration using high‐intensity laser pulses, at 10 16  W/cm 2 was studied irradiating different types of thin metal and plastic targets having 1‐micron thickness. The maximization of the proton energy process was investigated optimizing the laser parameters, the irradiation conditions and the target properties. Employing 600–700 J laser pulse energy, a focalization inducing self‐focusing effects and using targets with optimized thickness, it was possible to accelerate protons up to energies of above 8 MeV. The time‐of‐flight diagnostics has allowed to monitor the plasma properties and to control the ion acceleration process.